IMPROVING STUDENTS’ SPEAKING MOTIVATION USING MINGLE MUSIC TECHNIQUE - Ilinawati Ilinawati; Sijono Sijono (Journal of English Educational Study (JEES), 2020)
The main focus of this study is boosting students’ speaking ability by using mingle music technique. The data were taken from  the second semester students of English Language  Study program of STKIP Persada Khatulistiwa Sintang , in Academic  Year 2018/2019 which consisted of  22 students. A classroom action research design was employed in this research. In collecting the data, researchers used observation checklist, field note, and interview The research was conducted in two cycles, where in each cycle consisted of 1 meeting. It took 150 minutes for 3sks.The result showed that the students’ involvement in teaching learning process  improved from cycle 1 to cycle 2.Mingle music technique engaged the students to be more active in the classroom. It enable the students to have more practises in speaking with diffrent students and material. It can be concluded that the implementation of mingle music technique succeeded boosting students’ speaking ability.Keywords: Mingle Music Technique, Students’ Speaking Ability.